1984
DOI: 10.1002/ejsp.2420140302
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social motives, communication and group size on behaviour in an N‐person multi‐stage mixed‐motive game

Abstract: Two experiments investigated the impact of social motives or individuals' preferences for specific self-other outcome distributions, on behaviour in an n-person game. Subjects' social motives (altruistic, cooperative, individualistic, competitive)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
315
2
15

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(340 citation statements)
references
References 35 publications
8
315
2
15
Order By: Relevance
“…For example, for situations in which the total benefit is fixed-such as in a dictator game (Camerer and Thaler 1995)-a concern for the total benefit is irrelevant, and concern for the other's benefit should play the major role. As a result, people should take less from close others (Liebrand 1984). However, for situations in which the total benefit is not fixed and taking increases the total benefit, concern for the total benefit should prompt increased taking from close others.…”
Section: When Closeness Decreases Versus Increases Takingmentioning
confidence: 99%
“…For example, for situations in which the total benefit is fixed-such as in a dictator game (Camerer and Thaler 1995)-a concern for the total benefit is irrelevant, and concern for the other's benefit should play the major role. As a result, people should take less from close others (Liebrand 1984). However, for situations in which the total benefit is not fixed and taking increases the total benefit, concern for the total benefit should prompt increased taking from close others.…”
Section: When Closeness Decreases Versus Increases Takingmentioning
confidence: 99%
“…Only one previous study (Liebrand, 1984) reported an effect of social motives on choice behavior in an n-person game and that study used only one measurement technique in one location. The present study can be regarded as an extension of the Liebrand (1984) study.…”
mentioning
confidence: 99%
“…Only one previous study (Liebrand, 1984) reported an effect of social motives on choice behavior in an n-person game and that study used only one measurement technique in one location. The present study can be regarded as an extension of the Liebrand (1984) study. It is expected that the amount of money taken for self in the Sequence Dilemma is least for altruists, next lowest for cooperators, higher yet for individualists and greatest for competitors.…”
mentioning
confidence: 99%
“…In the first experiment, the decomposed game technique (Liebrand, 1984;Offerman et al, 1996;Park, 2000;Brosig, 2002) was used to assess an individual's value orientations. Participants played 24 decomposed games.…”
Section: Design Of the Preference Elicitation Experimentsmentioning
confidence: 99%
“…To obtain information about the intrinsic social preferences of our subjects, prior to the public goods game, we measure individual "value orientation" (i.e., the weight an agent attaches to her own well-being in comparison to the others' well-being) by means of the decomposed game technique (Griesinger and Livingston, 1973;Liebrand, 1984). 6 The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%